2011
DOI: 10.1007/s00441-011-1191-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comparison of telomere length, telomerase and reverse transcriptase activity and gene expression in human mesenchymal stem cells and cancer cells of various origins

Abstract: We have characterized and compared the telomere length, telomerase, reverse transcriptase (RT) activity and expression of genes implicated in cancer and in pluripotency, in human mesenchymal stem cells (MSCs) derived from dental papilla tissue, umbilical cord matrix and adipose tissue and in cancer cells (MDA-MB-231, U-87 MG, and MCF-7). MRC-5 fetal fibroblasts and adult muscle cells were used as somatic cell controls. Telomere length was significantly (P<0.05) higher in MSCs and somatic cells (7.2-9.3 kb) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 36 publications
1
60
1
Order By: Relevance
“…Contrary, in previous study, hTERT has been proposed to have a role in the upregulation of pluripotency marker expression in MSCs [35] . Although expression of pluripotency markers in adult stem cells is demonstrated in many studies [33,36] , their role is still not well defined.…”
Section: Research Highlightscontrasting
confidence: 58%
“…Contrary, in previous study, hTERT has been proposed to have a role in the upregulation of pluripotency marker expression in MSCs [35] . Although expression of pluripotency markers in adult stem cells is demonstrated in many studies [33,36] , their role is still not well defined.…”
Section: Research Highlightscontrasting
confidence: 58%
“…Survivin expression, which is documented in both gliomas and medulloblatomas [36,37], inhibits caspase activation, leading to the negative regulation of apoptosis in tumor cells [38]. Telomerase is a ribonucleoprotein that maintains the length of telomeres and thus controls cell proliferation [39], and high telomerase activity has been documented in brain tumor cells [40,41], particularly brain tumor stem cells [42]. The expression of cytomegalovirus (CMV) antigens IE1 and pp65 have been identified in glioma tissue, and in very low to undetectable levels in non-tumor tissue in the brain [43].…”
Section: Glioma Immunologymentioning
confidence: 99%
“…In addition to MSCs isolated from the bone marrow, many groups have isolated MSCs from various tissues and organs of the body, which exists there, for regenerating damaged tissues. Till recently, human-derived MSCs were isolated from diverse tissues such as adipose, skin, umbilical cord matrix, dental pulp/papilla and others have fully demonstrated the cellular properties of MSCs for clinical and research applications (Jeon et al 2011a(Jeon et al , 2011bAkiyama et al 2012;Karaoz et al 2013). The various types of MSCs exhibited similar fibroblasts-like morphology and growth pattern following attachment onto plastic culture plates (Jeon et al 2011a(Jeon et al , 2011b.…”
Section: Introductionmentioning
confidence: 99%
“…Further, it has been demonstrated that cells derived from dental tissues with the developing third molar (wisdom tooth) bud are a unique source of MSCs (Jeon et al 2011a(Jeon et al , 2011bPatil et al 2014). In our previous studies, MSCs derived from dental papilla tissue (DPSCs) of third molars showed outstanding cellular properties, telomerase activity, length of telomeric repeats, reverse transcriptase activity, cluster of differentiation (CD) surface markers and expression of transcripts, compared to those of bone marrow MSCs, adipose MSCs and dental pulp/ follicle MSCs (Jeon et al 2011a(Jeon et al , 2011b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation